2001
DOI: 10.1002/app.1479
|View full text |Cite
|
Sign up to set email alerts
|

Peroxide modification of poly(butylene adipate‐co‐succinate)

Abstract: We attempted to introduce crosslinking into poly(butylene adipate-co-succinate) (PBAS) to improve the properties, such as the mechanical strength and elasticity, by a simple addition of dicumyl peroxide (DCP). Prior to curing, the thermal stability of PBAS was investigated. Above 170°C PBAS was severely degraded, and the degradation could not be successfully stabilized by an antioxidant. The PBAS was effectively crosslinked by DCP, and the gel fraction increased as the DCP content increased. A major structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…This is probably responsible for an increase in the thermal stability of crosslinked PCL. Similar results were also reported for the crosslinking of poly(butylenes adipate‐ co ‐succinate) by Kim et al27…”
Section: Resultssupporting
confidence: 89%
“…This is probably responsible for an increase in the thermal stability of crosslinked PCL. Similar results were also reported for the crosslinking of poly(butylenes adipate‐ co ‐succinate) by Kim et al27…”
Section: Resultssupporting
confidence: 89%
“…Them ost common approach toward the CÀHf unctionalization of aliphatic polyesters is HATreactions initiated by thermolysis of ap eroxide.F or example,a ni mprovement in the mechanical properties of poly(butylene succinate) (PBS) at high temperature was observed through cross-linking reactions initiated by the thermolysis of DCP. [150,151] Detailed characterization of the reaction demonstrated that the gel content of the cross-linked material plateaued at 80 wt %and the storage modulus,l oss modulus,a nd complex viscosity improved after cross-linking. [152] To achieve more efficient cross-linking,P BS was also cross-linked in the presence of at rifunctional acrylate to produce polyester foams by melt blowing.…”
Section: Aliphatic Polyestersmentioning
confidence: 99%
“…Die gängigste Methode zur C‐H‐Funktionalisierung von aliphatischen Polyestern sind HAT‐Reaktionen, die durch Thermolyse eines Peroxids ausgelöst werden. Beispielsweise wurde eine Verbesserung der mechanischen Eigenschaften von Poly(butylensuccinat) (PBS) bei hohen Temperaturen durch Vernetzungsreaktionen, die durch Thermolyse von DCP ausgelöst wurden, beobachtet . Die detaillierte Charakterisierung der Reaktion zeigte, dass sich der Gelgehalt des vernetzten Materials auf 80 Gew.‐% einpendelte und sich der Speichermodul, der Verlustmodul und die komplexe Viskosität nach der Vernetzung verbesserten .…”
Section: Aliphatische Polyesterunclassified